Asylum, Immigration Restrictions and Exploitation: Hyper-precarity as a lens for understanding and tackling forced labour - Lewis, Hannah; Waite, Louise (Anti-Trafficking Review, 2015)
The topic of forced labour is receiving a growing amount of political and policy attention across the globe. This paper makes two clear contributions to emerging debates. First, we focus on a group who are seldom explicitly considered in forced labour debates: forced migrants who interact with the asylum system. We build an argument of the production of susceptibility to forced labour through the United Kingdom’s (UK) asylum system, discussing the roles of compromised socio-legal status resulting from restrictive immigration policy, neoliberal labour market characteristics and migrants’ own trajectories. Second, we argue that forced labour needs to be understood as part of, and an outcome of, widespread normalised precarious work. Precarity is a concept used to describe the rise of insecure, casualised and sub-contracted work and is useful in explaining labour market processes that are conducive to the production of forced labour. Using precarity as a lens to examine forced labour encourages the recognition of extreme forms of exploitation as part of a wider picture of systematic exploitation of migrants in the labour market. To understand the reasons why forced migrants might be drawn into severe labour exploitation in the UK, we introduce the concept of hyper-precarity to explain how multidimensional insecurities contribute to forced labour experiences, particularly among forced migrants in the global north. Viewing forced labour as connected to precarity also suggests that avenues and tools for tackling severe labour exploitation need to form part of the wider struggle for migrant labour rights.